A population study comparing tracheal and lung adenoid cystic carcinoma - Yu Gu; Songtao Lai; Yang Wang; Juan Yang; Ping Zhou; Tianxiang Chen (Cancer Medicine, 2024)
Abstract Background Thoracic adenoid cystic carcinoma (ACC) is rare, and the differences between tracheal and lung lesions have not been fully understood. Methods Patients were identified from a Chinese cancer center (FUSCC) (2005–2022) and the Surveillance, Epidemiology, and End Results (SEER) database (2000–2019). Incidence was calculated and trends were quantified. Clinicopathological features and overall survival (OS) were analyzed. Nomograms predicting OS were constructed. Results Totally, 55 tracheal adenoid cystic carcinoma (TACC) and 25 lung and bronchus adenoid cystic carcinoma (LACC) were included in a Chinese cohort, 121 TACC and 162 LACC included in the SEER cohort. There were larger tumor sizes, more lymph nodes and distant metastases for LACC than TACC patients. TACC patients are more likely to get local treatments. Patients with LACC had significantly worse median OS than patients with TACC (SEER cohort: 68.0 months vs. 109.0 months, p = 0.001, Chinese cohort: 62.9 months vs. 124.8 months, p = 0.061). Age, lymph node metastasis, distant metastasis and local treatment were identified as independent prognostic factors for OS of TACC. Distant metastasis and local treatment were identified for LACC. Specifically, surgery alone or in combination with radiotherapy is crucial for improving survival in both TACC and LACC. Only TACC benefits from radiotherapy alone, while chemotherapy does not improve survival for either. The nomograms constructed using these factors revealed good prognostic accuracy. Conclusions LACC is more aggressive and has a worse prognosis than TACC. TACC patients have more opportunities for local treatment, which is important for the prognosis of both TACC and LACC. Nomograms were created for TACC and LACC to aid in personalized survival predictions and clinical decisions.